MULTIMEDIA TEXTBOOK FOR 4TH YEAR OF PRIMARY SCHOOLS - OLEKŠÁKOVÁ, Monika; ÖLVECKÝ, Miroslav (Trends in education, 2010)
The starting point of this paper is creating a multimedia textbook for fourth year primary schools in the Department and information technologies. The authors deal with the subject of the working classes and the modern means of education such as multimedia textbook.
Keywords: manual training; educational resources; multimedia textbook.